Pupils Creative Activity in Textile Art at Competition - Urdziņa-Deruma, Māra; Kokina-Lilo, Mārīte (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The open olympiads of home economics and technologies encourage pupils of grades 5-9 to be creative in applying textile techniques. They also popularize textile art. Purpose of the study is to analyse the results of pupils’ creative work during the 10th open olympiad of home economics and technologies. Method: analysis of textile works. 376 pupils’ works from the 1st round and 85 works of the 2nd round have been analysed and assessed according to the following criteria: compliance with the task, unity of composition, composition of colours, compatibility of materials, originality, quality of the technical accomplishment, functionality. In the olympiad traditional Latvian handicraft techniques and materials as well as elements of other cultures and modern materials have been used. The originality of works submitted for the 1st round is expressed in seek of untraditional forms, techniques and combination of materials. The analysis performed on the 2nd round of works reveals that creativeness appears in the selection of materials, attuning and combining techniques to a greater extent than in the design of composition.